Decree-Law of the President of the Arab Republic of Egypt No. 97 of the Year 2015 On Amending Some Provisions of Law No. 62 of the Year 1975 With Regard to Illicit Gains = قرار رئيس جمهورية مصر العربية بالقانون رقم 97 لسنة 2015 بتعديل بعض أحكام القانون رقم 62 لسنة 1975 فى شأن الكسب غير المشروع - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic